COMPARATIVE CARRY OUT OF ADHESION OF THE ADHESIVE FILMS FORMED BY CARBAMIDEFORMALDEHYDE AND ACETATE POLYMER ADHESIVES (Innovation in Woodworking Industry and Engineering design, 2026)
This report experimentally examined adhesion of adhesive films formed by carbamideformaldehyde and polyvinilacetate adhesives to wood. It is influence of some factors (roughness gluing surfaces, specific pressure, temperature) on the values of adhesion. For this purpose used test fixtures from beech wood, glue carbamidformaldehyde PREFERE 4114 and polyvinilacetate polymer adhesive Jowacoll 124.00. Strength of adherence was defermined under the regulation of EN 302 and BS EN 205.